Students’ Reception To Creation Puppet Music Of Hikayat Banjar - Sani, Muhammad Budi Zakia; Alfianti, Dewi (Universitas Negeri Semarang, 2021)
Hikayat Banjar as a literary treasure with a mix of history and myths about the origin of the Banjar people is not well known to the younger generation of South Kalimantan. In fact, from the Hikayat Banjar, we can know the central role of the river as a wetland landscape. This research tries to revitalize the Hikayat Banjar in the form of a puppet creation video that contains the final part of the Hikayat Banjar music which is related to the history of the founding of the Banjar kingdom. This video was shown and watched by students of SMA Islam Terpadu Ukhuwah class XI. After watching the video, they were asked to answer questions about how they saw the show about the Hikayat Banjar which they had watched. From the results, it is known that there is a great relationship between Hikayat Banjar and the students' knowledge about the show. It is proven, only 56% of students know about Hikayat Banjar. However, this video itself was received positively by students and became their reference in understanding certain parts of the Banjar Hikayat.Meanwhile, the role of the river in the Hikayat Banjar is considered important by the respondents. Ninety-six percent of respondents agree that rivers play an important role, both socially and politically. Both are a means of regional development, as well as a battle arena. This study uses a descriptive approach to describe and view audience data in the questionnaire that has been filled out. The results show how Hikayat Banjar music position is on the horizon of audience reception.